2023
DOI: 10.1126/sciadv.ade0008
|View full text |Cite
|
Sign up to set email alerts
|

Designing and identifying β-hairpin peptide macrocycles with antibiotic potential

Abstract: Peptide macrocycles are a rapidly emerging class of therapeutic, yet the design of their structure and activity remains challenging. This is especially true for those with β-hairpin structure due to weak folding properties and a propensity for aggregation. Here, we use proteomic analysis and common antimicrobial features to design a large peptide library with macrocyclic β-hairpin structure. Using an activity-driven high-throughput screen, we identify dozens of peptides killing bacteria through selective membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…DTr18-dab followed a similar trend in propidium uptake as melittin, but it is not as potent in the same time frame. The main target of kanamycin is the ribosome, but it has reported that membrane perturbation can also occur. ,− However, no membrane damage from kanamycin is observed compared to our PBS control under our conditions. ,− …”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…DTr18-dab followed a similar trend in propidium uptake as melittin, but it is not as potent in the same time frame. The main target of kanamycin is the ribosome, but it has reported that membrane perturbation can also occur. ,− However, no membrane damage from kanamycin is observed compared to our PBS control under our conditions. ,− …”
Section: Resultsmentioning
confidence: 55%
“…Loss of peptide sequence abundance can be measured by changes in plasmid number in culture to reveal putative antimicrobial peptide leads. [20][21][22]33,34 From one of these screens, a peptide sequence was discovered that had antimicrobial activity against Escherichia coli W3110. The peptide was designated Tcp18 and, when chemically synthesized and assayed, had a minimum inhibitory concentration (MIC) of 16 μg/mL against both E. coli W3110 and E. coli ATCC 25922 in Muller Hinton broth (MH).…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1C, Table S2). This group had a diverse range of charge (3.88-11.88), length (14)(15)(16)(17)(18) amino acids), and potential cysteine pairs (1-3) (Fig. 1D).…”
Section: Slay Identifies Serum Active Synthetic Antimicrobial Peptidesmentioning
confidence: 99%